2014
DOI: 10.6001/biologija.v60i3.2971
|View full text |Cite
|
Sign up to set email alerts
|

The use of Acinetobacter sp. for oil hydrocarbon degradation in saline waters

Abstract: This paper describes the problem of oil pollutant re moval and the use of Acinetobacter genus microor ganisms in oil biodegradation. As part of the experi ments, Acinetobacter genus microorganism strain with the best ability to degrade crude oil and fuel oil in saline waters was selected from the microorganism collection of JSC "Biocentras". The impact of environmental con ditions (salinity, temperature, pH, substrate concent ration) on this strain's viability and the efficacy of its oil degradation processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Also, a decrease in the absorbance of UV-visible spectrum of PAH incubated separately with each species of Acinetobacter gives another evidence of degradation of PAH by the two studied species; this indicates that degradation of PAH occurred as bacteria uses it as carbon source and energy. It is worthwhile to mention that oil-degrading Acinetobacter produces an extracellular polyanionic, heteropolysaccharide bioemulsifier termed emulsan consisting of high-molecular-mass polysaccharides associated with proteins which also stabilizes oil-water and water-oil emulsions (Toren et al, 2001;Margesin et al, 2013;Fatajeva et al, 2014 ). The study also revealed that using mineral medium without addition of nutrients was adequate for enhancing bacterial growth and degradation activity of both species of Acinetobacter.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Also, a decrease in the absorbance of UV-visible spectrum of PAH incubated separately with each species of Acinetobacter gives another evidence of degradation of PAH by the two studied species; this indicates that degradation of PAH occurred as bacteria uses it as carbon source and energy. It is worthwhile to mention that oil-degrading Acinetobacter produces an extracellular polyanionic, heteropolysaccharide bioemulsifier termed emulsan consisting of high-molecular-mass polysaccharides associated with proteins which also stabilizes oil-water and water-oil emulsions (Toren et al, 2001;Margesin et al, 2013;Fatajeva et al, 2014 ). The study also revealed that using mineral medium without addition of nutrients was adequate for enhancing bacterial growth and degradation activity of both species of Acinetobacter.…”
Section: Resultsmentioning
confidence: 89%
“…Zaki et al (2015) reported that crude oil degradation is faster in warm water because the heat generated within the water body will further encourage the breakdown of the spilled petroleum through natural processes such as evaporation. Besides, Fatajeva et al (2014) reported that H.T. Al-Hadithi et al Acinetobacter is the most active bacteria to degrade crude oil and fuel oil at a temperature of 30 °C, in a pH range of 7-8, in model ocean water of 35 ‰ salinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports about degradation of environmental pollutants by Acinetobacter sp. (Fatajeva et al, 2014;Kim et al, 2003;Abdel-El-Haleem, 2004), but FE-degrading strain was isolated from the genus for the first time.…”
Section: Degradation Of Fe and Other Aopp Herbicides By Strain Dl-2mentioning
confidence: 97%
“…Bioremediation of polluted environments is based on contaminant biodegradation, that is, metabolic abilities of microorganisms to transform or mineralize organic contaminants into less harmful, nonhazardous substances, which are further integrated into natural biogeochemical cycles [5,14,20]. The spectrum of microorganisms used for hydrocarbons degradation mostly includes the actinobacteria of Rhodococcus, Dietzia, Gordonia genera as well as bacteria of Pseudomonas, Arthrobacter and Acinetobacter genera [7,12,14,15]. Many authors have determined that these microorganisms are widely spread in oil-polluted ecosystems where hydrocarbon-oxidizing actinobacteria play a significant role, which is explained by metabolic peculiarities of these bacteria and their resistance to unfavourable conditions [9,14].…”
mentioning
confidence: 99%